The 10 laws of career reinvention : essential survival skills for any economy - Mitchell, Pamela , 1964- (Penguin Books, 2010)
America?s Reinvention Coach offers readers the tools they need to navigate the full arc of career change. Part I introduces the Reinvention Mindset while Part II offers real-life stories of individuals who have made the leap to new careers.